2016
DOI: 10.1080/03079457.2015.1137866
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous live infectious bronchitis virus vaccination in day-old commercial broiler chicks: clinical signs, ciliary health, immune responses and protection against variant infectious bronchitis viruses

Abstract: Groups of one-day-old broiler chicks were vaccinated via the oculo-nasal route with different live infectious bronchitis virus (IBV) vaccines: Massachusetts (Mass), 793B, D274 or Arkansas (Ark). Clinical signs and gross lesions were evaluated. Five chicks from each group were humanely killed at intervals and their tracheas collected for ciliary activity assessment and for the detection of CD4+, CD8+ and IgA-bearing B cells by immunohistochemistry (IHC). Blood samples were collected at intervals for the detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 50 publications
4
47
2
2
Order By: Relevance
“…Ciliostasis results in the current study highlighted excellent IBV protection against M41 and QX challenges in groups receiving H120 + 793B, or the same IBV vaccines given along with aMPV or NDV vaccines. Previous work has shown that the combination of Mass + 793B conferred excellent ciliary protection against Asian (QX and Q1) and Middle East (IS/1494/06 and IS/885/00) IBV strains [25,[48][49][50][51]. When IBV H120 and CR88 Table 5 Experiment 2: IBV or aMPV detections from trachea and kidney samples at 5 days post M41 or virulent aMPV challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Ciliostasis results in the current study highlighted excellent IBV protection against M41 and QX challenges in groups receiving H120 + 793B, or the same IBV vaccines given along with aMPV or NDV vaccines. Previous work has shown that the combination of Mass + 793B conferred excellent ciliary protection against Asian (QX and Q1) and Middle East (IS/1494/06 and IS/885/00) IBV strains [25,[48][49][50][51]. When IBV H120 and CR88 Table 5 Experiment 2: IBV or aMPV detections from trachea and kidney samples at 5 days post M41 or virulent aMPV challenge.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the IBV vaccine can induce mild signs (such as nasal discharge) of IB shortly after administration (Matthijs et al, 2003(Matthijs et al, , 2005(Matthijs et al, , 2008, and increases the susceptibility of 4-week-old broilers to colibacillosis to a similar extent as the virulent IBV strain (Matthijs et al, 2005). In addition, the variable virulence of the vaccine viruses when they are coadministered and the ability of some of the combinations to cause severe tracheal damage have been reported (Awad et al, 2016). Most of the diseased broilers in which IBV vaccine-like viruses were isolated in this study showed mild to severe colibacillosis when they were approximately 4 weeks old.…”
Section: Discussionmentioning
confidence: 99%
“…IS/1494/06 challenge [33]. Awad et al showed that one-day-old chicks vaccinated with two different mixtures of Mass + 793/B produced 92% and 68% ciliary protection against QX challenge [11]. Mohammadi et al showed a protective ability of the used vaccination program.…”
Section: Discussionmentioning
confidence: 99%
“…Among a large number of serotypes or variants emerged after the first documentation of IBV in 1931, Massachusetts 41 (M41) and 793/B serotypes have been expanded through the world and commercial vaccines are available against both serotypes providing a broad crossprotection against many different IBV types when used together [7][8][9]. Despite vaccination efforts, novel field IBVs continue to emerge; some antigenic variants may subsequently become dominant which makes prevention of IBV infections very challenging [10,11]. Similar to what has been happening in Iranian poultry farms leading to unceasing IB outbreaks despite extensive vaccination.…”
Section: Introductionmentioning
confidence: 99%